2014
DOI: 10.14814/phy2.12142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin C and E supplementation on endogenous antioxidant systems and heat shock proteins in response to endurance training

Abstract: Reactive oxygen and nitrogen species are important signal molecules for adaptations to training. Due to the antioxidant properties of vitamin C and E, supplementation has been shown to blunt adaptations to endurance training. In this study, we investigated the effects of vitamin C and E supplementation and endurance training on adaptations in endogenous antioxidants and heat shock proteins (HSP). Thirty seven males and females were randomly assigned to receive Vitamin C and E (C + E; C: 1000 mg, E: 235 mg dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…() did not observe any effect of vitamin C/E supplementation on increases in muscle SOD2 protein expression following 12 weeks of training, while Cumminings et al . ( b ) saw little effect of either exercise training or antioxidant supplementation on Gpx1 or SOD2 expression. It appears, therefore, that antioxidant supplementation is detrimental to acute exercise antioxidant response and can impair endurance training‐induced increases in antioxidant enzyme mRNA levels, but the effects on endogenous antioxidant enzyme activities and protein levels following training are not clear.…”
Section: Reactive Oxygen Species and Exercise Trainingmentioning
confidence: 95%
“…() did not observe any effect of vitamin C/E supplementation on increases in muscle SOD2 protein expression following 12 weeks of training, while Cumminings et al . ( b ) saw little effect of either exercise training or antioxidant supplementation on Gpx1 or SOD2 expression. It appears, therefore, that antioxidant supplementation is detrimental to acute exercise antioxidant response and can impair endurance training‐induced increases in antioxidant enzyme mRNA levels, but the effects on endogenous antioxidant enzyme activities and protein levels following training are not clear.…”
Section: Reactive Oxygen Species and Exercise Trainingmentioning
confidence: 95%
“…We have previously shown that vitamin C and E supplementation did not have an effect on HSP levels in response to 11 weeks of endurance training [24]. To our knowledge, adaptation mechanisms in the HSPs, and GPx1 and mnSOD, in response to heavy load strength training in combination with vitamin C and E supplementation has not been investigated yet in humans.…”
Section: Introductionmentioning
confidence: 91%
“…A minor decrease in the concentration of uric acid was also detected in group III (vitamins E + C). Previously, a decrease in the concentration of serum uric acid was detected in young adults who consumed vitamins C and E for 11 weeks [50] . Thus age, gender and an increased intake of antioxidant supplements may have an effect on the levels of uric acid in blood.…”
Section: Discussionmentioning
confidence: 96%
“…Our observations may indicate that individuals in group II (omega-3) can become prone to increased oxidative stress due to decreased concentration of uric acid. In the meantime, it is worth noting that increased concentration of serum uric acid may be linked to increased risk for gout and some other diseases in some populations [50][51][52][53] .…”
Section: Discussionmentioning
confidence: 99%